Data retrieval service on poverty blockchain-based on regional government - Koniyo, Moh Hidayat; Sudarma, Made (Association for Scientific Computing Electrical and Engineering, 2020)
The distribution of assistance to disadvantaged people in an area is always synonymous with problems especially, in the duplication of assistance and manipulation of family data that actually has no right to obtain assistance data for underprivileged families. To ensure the integrity of the data taken is not duplicated and non-repudiation, the blockchain-based poverty data collection plan is one solution. The purpose of this research is to ensure that the data retrieved cannot be modified after data retrieval and the database cannot validly deny that the data has been provided as a result of a particular request. The feasibility of the proposed service using the blockchain method is a request from the poverty database in the form of low-income family data and assistance type data that are placed in the blockchain series and tested with hash values that have been created from the blockchain